Sosialisasi dan Pelatihan Pemanfaatan Limbah Menjadi Barang yang Berguna Di MTS Alwashliyah Gedung Johor - Ichpan Zulfansyah; Yenni Novita Harahap (KREATIF: Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2025)
Waste is an environmental problem that continues to increase along with population growth and human consumptive activities. Without proper management, waste can cause negative impacts such as pollution and flooding. This community service activity was carried out at MTs Al Washliyah Gedung Johor, Medan Johor District, Medan City, targeting seventh grade students. The objective of the activity was to raise awareness from an early age about the importance of maintaining environmental cleanliness through socialization and training in recycling plastic waste from mineral water bottles into useful and economical handicrafts. The activity methods included site observation, material socialization, and practice making crafts from plastic waste. The results of the activity showed high enthusiasm and increased student understanding of waste management. This activity is expected to foster creativity and environmental awareness in participants, while encouraging the formation of a generation that cares about cleanliness and environmental sustainability.